The role of antiepileptic drugs in free radicals generation and antioxidant levels in epileptic patients - Eldin, Essam Eldin Mohamed Nour; Elshebiny, Hosam Abdel-Fattah; Mohamed, Tarek Mostafa; Abdel-Aziz, Mohamed Abdel-Azim; Readi, Mahmoud Zaki el (The international journal of neuroscience, 2016)
Many risk factors are encountered during the pathogenesis of epilepsy. In this study, the effect of seizure frequency on free radical generation and antioxidants levels in epileptic patients was evaluated. This study was carried out on 15 healthy controls (GI) and 60 epileptic patients treated with mono- or poly-therapy of carbamazepine, valproic acid, or phenytoin. The treated epileptic patients were divided into 2 main groups according to the seizure frequency: controlled seizure patients GII (n = 30) and uncontrolled seizure patients GIII (n = 30). GII included the GIIA subgroup (n = 15) which had been seizure free for more than 12 months and the GIIB subgroup (n = 15) which had been seizure free for a period from 6 to12 months. GIII included GIIIA (n = 15) and GIIIB (n = 15) for patients which had a seizure frequency of less than and more than four times/month, respectively. In comparison to the control group (GI), the levels of nitric oxide (NO) and malondialdehyde/creatinine ratio were significantly increased in GIIB, GIIIA, and GIIIB, while vitamins A and E levels were significantly decreased in GIIIB. Serum NO levels had significant negative correlations with serum vitamin E in the GIIA and GIIB groups, and with vitamin A in the GIIIA and GIIIB groups. However, serum NO had positive correlation with urinary MDA/Cr ratio. The imbalance between free radical generation and antioxidant system in epileptic patients may be a factor in seizure frequency.
Gesehen am 06.05.2020